Effect of Balloon Angle on the Hairiness and other Yarn Properties of Polyester Ring Spun Yarn - (:unkn) unknown (INST CHEMICAL FIBRES, 2008)
In this research the effects of the yarn balloon angle on yarn hairiness and other yarn properties was investigated The yarn balloon was changed by rise of five different weights of C ope travellers. The Yarn counts chosen were 15 tex, 20 tex and 30 tex. Three spindle speeds were used: 9,000 r.p.m., 10,000 r.p.m. and 11,000 r.p.m. Yarn hairiness, yarn count, balloon angle, yarn surface helix angle, yarn twist, strength and elongation at break, as well as irregularity and imperfection tests were carried out for all the Yarn samples. In this research it was noted that as the balloon angle increases, the Yarn hairiness and yarn surface helix angle increase. Other yarn properties were also investigated and discussed.
Keywords: balloon angle; yarn hairiness; yarn properties; traveller weight; yarn tension; FIBER PROPERTIES